A Novel Mesh Routing Using the Nodes with Identical Tree Level. (24th November 2014) - Yuan, Li-yong; Xu, Lin; Zhu, Yi-hua; Sun, Cong
Contemporary wireless sensor network (WSN) adopts IEEE 802.15.4 in its MAC and PHY layers. The mesh routing introduced in IEEE 802.15.5 standard, referred to as the basic mesh routing below, improves reliability and robustness of routing in WSNs since there are multiple routes from a node to the sink. In this paper, the mesh routing with identical level (MRIL) is proposed, which constructs the mesh using the tree generated per IEEE 802.15.5 standard, the two-hop neighbors of the nodes, and the nodes in the same level chains with each consisting of the nodes having identical tree level. The MRIL outperforms the basic mesh routing in terms of energy consumption, the average number of hops traversed per packet, the sizes of memory used to keep neighbor lists and connectivity matrices at nodes, and the number of packet transmissions in exchanging link state information.